Host upregulation of lipid droplets drives antiviral responses - Ebony A. Monson; Karla J. Helbig (Cell Stress, 2021)
When a host cell is infected by a virus, it activates the innate immune response, setting off a cascade of signalling events leading to the production of an antiviral response. This immune response is typically robust and in general works well to clear viral infections, however, viruses have evolved evasion strategies to combat this, and therefore, a better understanding of how this response works in more detail is needed for the development of novel and effective therapeutics. Lipid droplets (LDs) are intracellular organelles and have historically been thought of simply as cellular energy sources, however, have more recently been recognised as critical organelles in signalling events. Importantly, many viruses are known to take over host cellular production of LDs, and it has traditionally been assumed the sole purpose of this is to supply energy for viral life cycle events. However, our recent work positions LDs as important organelles during the first few hours of an antiviral response, showing that they underpin the production of important antiviral cytokines following viral infection. Following infection of cells with either RNA viruses (Zika, Dengue, Influenza A) or a DNA (Herpes Simplex Virus-1) virus, LDs were rapidly upregulated, and this response was also replicated following stimulation with viral mimic agonists. This upregulation of LDs following infection was transient, and interestingly, did not follow the well described homeostatic mechanism of LD upregulation, instead being controlled by EGFR. The cell’s ability to mount an effective immune response was greatly diminished when inhibiting EGFR, thus inhibiting LD upregulation during infection, also leading to an increase in viral replication. In this microreview, we extrapolate our recent findings and discuss LDs as an important organelle in the innate immune response.